2008
DOI: 10.1111/j.1439-0531.2008.01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of Microarray Technology to Profile Gene Expression Patterns Important for Reproduction in Cattle

Abstract: Fertility in cattle is a major component of many agricultural enterprises and there is pressure to devise methods to improve this. A number of approaches are ongoing, one of which is to better understand the cellular and molecular events of the development of reproductive tissues and to use these as targets for developing new strategies. Microarray technologies now allow us the potential to determine the transcriptional profile of expressed genes in a given tissue. This review focuses on the types of microarra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 81 publications
1
10
0
Order By: Relevance
“…Thus, both the causing variable, most probably a factor secreted by the early embryo, and the purpose of the enhancement remain to be shown. By cautiously extrapolating in vitro findings, these results point towards an earlier maternal recognition of pregnancy appearing locally than previously described (Evans et al, 2008). Further studies are indicated.…”
supporting
confidence: 59%
“…Thus, both the causing variable, most probably a factor secreted by the early embryo, and the purpose of the enhancement remain to be shown. By cautiously extrapolating in vitro findings, these results point towards an earlier maternal recognition of pregnancy appearing locally than previously described (Evans et al, 2008). Further studies are indicated.…”
supporting
confidence: 59%
“…intra-genic mutations). Furthermore, knowledge of likely genes and biological pathways governing phenotypic differencing among animals are emerging from either genome-wide association studies (Berry et al, 2012), candidate gene studies (Waters et al, 2011) or transcriptomic studies (Evans et al, 2008). Such discoveries could be incorporated into a more supervised (e.g.…”
Section: Genomic Mating Plansmentioning
confidence: 99%
“…To facilitate the studies of changes in gene expression and move away from time-consuming procedures of SSH and subtracted cDNA libraries, the microarray technology developed in the 1990s to early 2000s (Fodor et al, 1993;Lockhart et al, 1996;Lipshutz et al, 1999;Kargul et al, 2001;VanBuren et al, 2002) proved very useful. Indeed, by now it is the most popular technique to study the dynamic changes of gene expression during early development (for recent reviews, see Adjaye, 2005;Aiba et al, 2006;Evans et al, 2008). At the same time, expansion of the genome sequencing projects for other chordate model organisms, together with production and representative sequencing of cDNA libraries from eggs or ovaries for these species permitted to add a second-phylogenetic-dimension to the studies of the oocyte cytoplasm's role in early development (Evsikov et al, 2006;Evsikov and Marin de Evsikova, 2009).…”
Section: Gene Expression During Oet: a Historical Perspectivementioning
confidence: 99%